Effect of thermal treatment, microwave, and pulsed electric field processing on the antimicrobial potential of açaí (Euterpe oleracea), stevia (Stevia rebaudiana Bertoni), and ginseng (Panax quinquefolius L.) extracts. (August 2018) - Pina-Pérez, Maria Consuelo; Rivas, Alejandro; Martínez, Antonio; Rodrigo, Dolores
Abstract: The antimicrobial potential of three functional ingredients, açaí ( Euterpe oleracea ), stevia ( Stevia rebaudiana Bertoni), and ginseng ( Panax quinquefolius L.), was assessed against sporeforming/non-sporeforming foodborne pathogens before and after processing. In vitro inhibitory effect of tested functional ingredients was significantly affected by the extract concentration (1–10% (w/v)) and the technology applied (microwave treatment (MW) (900 W 30 s), conventional thermal treatment (CT) (90 °C, 60 s) and non-thermal pulsed electric fields (PEF) (20 kV/cm, 270 μs)). Ginseng was the most stable ingredient with regard to CT, MW, and PEF application, maintaining or enhancing its antimicrobial capability after processing. The highest inhibition zone diameter of those obtained in the present study (15.11 ± 0.11 mm) is reflecting the promising potential of MW treated ginseng extracts (10% (w/v)) as antimicrobials against E. coli O157:H7. The PEF process significantly (p-value < 0.05) improved the antimicrobial bioactivity of stevia and açaí against Gram (+) and Gram (−) bacteria even applied at the lowest concentration level (1% (w/v)). New validation studies are required to assess the antimicrobial potential and the stability of other functional properties attributed to these ingredients to be integrated in novel formulated matrices processed by conventional and emerging food preservation technologies. Highlights: Açaí, ginseng, and stevia antimicrobial potential was assessed before/after processing. Açaí antimicrobial functionality was negatively affected by thermal treatment. MW-processed ginseng extract achieved the maximum inhibitory effect against E. coli O157:H7. Ginseng [1−10] % (w/v) extract functionality was the most stable after processing. PEF treatment was the most efficient technology improving antimicrobial stevia and açai spectrum.